2015
DOI: 10.1016/j.sbspro.2015.01.358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oil Revenue and the Sudan Economy: Econometric Model for Services Sector GDP

Abstract: This paper investigates the impact of oil revenue and the service GDP of Sudan for the period 2000 to 2012. To achieve this goal, secondary data were collected and analyzed using regression methods. The results reveal a causal relationship between oil revenue (independent variable) and service GDP (dependent variables). Regression analysis result suggests that oil revenue affects the service GDP positively. Oil revenue is estimated to have contributed to 78.8 percent of variation in GDP between 2000 and 2012. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 8 publications
(7 reference statements)
2
10
0
Order By: Relevance
“…Therefore, HO 1 is accepted while the study declines the alternate submission. The result confirms the findings of (Ologunde et al, 2020) but conflicts with the findings of (Hassan and Abdullah, 2015). Conversely, the t-statistic of tax revenue (TXRV) is 4.686 with a P = 0.00 <0.05.…”
Section: Robustness Checksupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, HO 1 is accepted while the study declines the alternate submission. The result confirms the findings of (Ologunde et al, 2020) but conflicts with the findings of (Hassan and Abdullah, 2015). Conversely, the t-statistic of tax revenue (TXRV) is 4.686 with a P = 0.00 <0.05.…”
Section: Robustness Checksupporting
confidence: 67%
“…However, Nigeria is at variance with all these components of social attainment. Hassan and Abdullah (2015) investigated the impact of oil revenue on the economy of Sudan from 2000 to 2012, using regression techniques. The outcome showed a causal relationship between oil revenue and service GDP.…”
Section: Social Developmentmentioning
confidence: 99%
“…However, weak diversification reduces the country's energy security and increases the risk of budget revenues. These problems have been described by various researchers as the impact of oil prices on the income of the exporting country, For example, Alekhina and Yoshino (2018) in the example of European countries, Heidarian and Green (1989) Al-Moneef (2006) in the example of Arab oil-exporting countries, Dreger and Rahmani (2014) on the example of the Iranian economy, Hassan and Abdullah (2014) on the example of the Sudanese economy, Olayungbo and Adediran (2017) on the example of Nigeriaç Humbatova and Hajiyev (2019) on the example of the Azerbaijani economy investigated this problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Brunnschweiler (2009) concluded with a positive and highly significant effect of oil on economic development in transition economies of the Former Soviet Union (FSU) and Central and Eastern Europe (CEE) between 1990 and 2006. Using the OLS method, Hassan and Abdullah (2015) investigated the impact of oil revenue and the service GDP of Sudan, found a positive effect of oil revenue on service GDP. A comparative study between Mexico and Indonesia on policy options implemented during the oil boom era, Usui (1997) observed that Indonesia implemented good macroeconomic policy framework, which surpass the occurrence of Dutch disease, while Mexico was unable to utilize the opportunity of the oil boom, which exerted a negative effect on growth.…”
Section: Relationship Between Oil Revenue and Economic Growthmentioning
confidence: 99%